DAMPAK JUDI ONLINE TERHADAP KESEHATAN MENTAL MAHASISWA - Wirareja, Yogi; Sa'adah, Nurus (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
Gambling is a pathological activity that is still carried out by many members of society, including students. Online gambling has become an increasingly disturbing phenomenon among college students, with potentially serious impacts on their mental health. This research aims to determine the impact of online gambling on mental health in students. This research is library research or Library Research which is carried out in order to collect information and data through various sources including journals, books, documents, mass media, and so on. The results of this study show that online gambling has a negative impact on the mental health of students, including causing stress, anxiety, depression, disturbed sleep patterns, dependency and decreased academic performance.